Implikasi Penggunaan Bahasa Indonesia Terhadap Bahasa Daerah Pada Siswa Kelas IV SDN 03 Kelabu - Intan Nur Aini; Ramona Fidella; Adrias Adrias; Fadhila Suciana (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
The ability to speak Indonesian is a crucial aspect of children's development, as it plays a significant role in learning, communication, and social interaction both in school and in the wider community. This study aims to analyze the impact of local language use on students’ Indonesian language proficiency, focusing on fourth-grade students at SDN 03 Kelabu. All 20 students in the class were selected as the research sample. This research employs a qualitative approach using observation and interviews to gather in-depth data regarding students’ daily language habits and their effects on classroom learning. The findings reveal that the dominant use of local languages at home and in the surrounding environment limits the students' ability to use Indonesian actively, particularly in formal learning contexts. This negatively affects their communication skills—both spoken and written—and hinders academic achievement. The study is analyzed through social learning theory and ecological systems theory, which explain that language development is influenced by interactions between individuals and their immediate environments, such as family, peers, and school. Based on these findings, it is recommended that teachers and parents actively encourage the use of Indonesian in daily activities, especially in educational settings. The study also provides suggestions for further research on strategies to improve Indonesian language proficiency in areas where local languages are predominantly spoken.